Human Capital Analysis at PT. Matahari Department Store Festive Walk Karawang - Gultom, Juniar Pratiwi; Jamaludin, Asep; Nandang, Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The purpose of this research is to analyze the human capital owned by PT Matahari Department Store Festive Walk Karawang. The application in creating human capital in the company includes five components, namely individual capability, individual motivation, the organization climate, workgroup effectiveness and leadership. Because of the importance of human capital in the progress of a company, companies need to pay attention to the application of human capital components to the maximum. The success of a company depends not only on technological excellence and the availability of funds, but also on existing human capital factors. From the observation, there are so many companies in Indonesia that have not maximized their human capital. The results showed that the application of components in creating human capital at PT Matahari Department Store Festive Walk Karawang is quite good.